The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1097/01.bpo.0000173246.12184.a5
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Accuracy of MRI Scanogram in the Evaluation of Limb Length Discrepancy

Abstract: The purpose of this study was to compare MRI scanogram with traditional radiographic methods for measurement of limb length. The authors hypothesized that MRI scanogram would be as reliable and accurate as radiographic scanogram in measurement of limb length without exposing patients to ionizing radiation. Twelve cadaveric femurs were measured using AP conventional radiographic scanogram, CT scanogram, MRI scanogram, and electronic caliper. Three orthopaedists performed two separate measurements using each tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Although an MRI scanogram does not expose patients to ionizing radiation, the measurements obtained using this technique are slightly less accurate than those obtained with a radiographic scanogram or a CT scanogram [25]. Furthermore, an MRI scanogram has not been well-studied in the clinical setting as an assessment tool for LLD, is probably more expensive, may require sedation in some children, typically requires a longer time to schedule and to complete the study, and may be contraindicated in patients with certain implantable devices.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although an MRI scanogram does not expose patients to ionizing radiation, the measurements obtained using this technique are slightly less accurate than those obtained with a radiographic scanogram or a CT scanogram [25]. Furthermore, an MRI scanogram has not been well-studied in the clinical setting as an assessment tool for LLD, is probably more expensive, may require sedation in some children, typically requires a longer time to schedule and to complete the study, and may be contraindicated in patients with certain implantable devices.…”
Section: Discussionmentioning
confidence: 93%
“…Several authors have reported the results of LLD measurement using a variety of imaging techniques such as orthoroentgenogram [13], CR-based teleoroentgenogram [38], slit scanogram [28], microdose digital radiography [3], CT scanogram [1,2,19], ultrasound [42], and MRI scanogram [25]. One needs to consider several issues such as reliability, accuracy, magnification, radiation dose, cost, need for special equipment, convenience, and opportunity to image the entire extremity when choosing the imaging technique for evaluating patients presenting with LLD (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several strategies have been described to assess LLD using different clinical and radiological methods. The degrees of precision and validity of certain methods such as computed tomography (CT) scanogram [1,2,14], X-ray scanogram [23] and magnetic resonance imaging (MRI) scanogram [18] are well documented. Unfortunately, the above-mentioned methods cannot be routinely used in THA patients due to the high cost as well as the artefacts encountered with the MRI scanogram because of the presence of a metal in the field of radiation.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity for detecting bony osteolytic lesions was 51.7% for radiography, 74.7% for computed tomography, and 95.4% for magnetic resonance imaging as reported by Walde et al [106]. Gender, age, BW, and waist girth (1) Using the therapeutic depth over safety depth ratio (T/S ratio) as the indicator of therapeutic depth (2) No significant difference in the T/S ratio between genders (3) The T/S ratio of these 12 acupuncture points ranged from 0.67 to 0.88 and increased significantly with body weight, age, and waist girth (4) The therapeutic depth of abdominal acupoints was closer to the safe depth in overweight and older children aged 7 to 15 (5) No significant difference between genders (1) Overweight group had the greatest de-qi depth (2) Points of female chest had greater depth than male (3) No correlations between the de-qi depth and electric resistance of each point Yet MRI scanogram is slightly less accurate compared with radiographic scanogram in detecting limb length differences [107]. In addition, we also found several studies discussing the divergence among different measuring tools when investigating various body tissues including adipose volume (visceral or subcutaneous), muscle thickness, bone loss, and cartilage thickness.…”
Section: Discussionmentioning
confidence: 99%